Ethical Leadership, at the Beginning of a Research - Barizsné Hadházi, Edit (International Journal of Engineering and Management Sciences, 2020)
In this study I deal with the ethical leadership. I give an insight into the approaches of ethical leadership, give a literature review on the concept of ethical leadership, and introduce the measurement methods used in the most important empirical researches related to this topic. I also try to report on the first results of my research (I plan to describe features of Hungarian leaders based on a smaller sample). How does this relate to the challenges of Industry 4.0? I give the answer from the fact that, with the advent of these new technologies (which in themselves have ethical questions), among these new challenges, the focus of the manager's attention will continue to be partly on their employees. If they set an ethical example for their subordinates, they encourage their employees to act ethically, which gives the company a competitive edge in many ways, both in the product/service market and in the labor market too. So, with my study, I would like to draw the attention of executives and managers to the fact that new technologies and the human factor together bring new successes, and that one possible way of doing this is by consciously managing their company ethically and developing an ethical organizational culture.